Responsibilities of Parents with Disabilities in Fulfilling Children's Rights: A Review of Islamic Law and Child Protection Law - Yaomi Arsy, Yasinta; Asyrof, Muhammad Najib (Qanun: Jurnal Hukum Keluarga Islam, 2024)
One of the juridical consequences arising from the agreement or legal bond of marriage between a man and a woman is the emergence of rights and obligations between both parties. One of their rights and obligations is to jointly fulfill the rights of the children resulting from the marriage. Although fulfilling the rights of the children is a duty for both parents, the situation becomes different when the parents face physical limitations, namely disabilities. In this context, they will strive harder to ensure the fulfillment of the children's rights. Considering the gap between the reality and the idealism of the law, this research aims to explore the efforts of parents with disabilities in fulfilling the rights of children in the Citangkil District of Cilegon City from the perspective of the Republic of Indonesia Law No. 35 of 2014 concerning Child Protection and Islamic Law. In line with the research objective, this study uses a qualitative method focusing on field facts, with a juridical approach. From this methodological approach, this research successfully reveals that various efforts made by parents with disabilities to fulfill the children's right to life, including working as massage therapists, farmers, entrepreneurs, traders, and waste collectors. In accordance with the Child Protection Law No. 35 of 2014 and Islamic Law, this research concludes that parents with disabilities have fulfilled the children's rights in accordance with the provisions of the law.